Analisis Produksi dan Air Limbah Industri Batu Alam dengan Perlakuan Eco-Enzym - Wahana, Siti; Eviyati, Raden; Amini, Zakiyah (Universitas Pekalongan, 2023)
This research aims to identify production processes that produce natural stone waste and determine the effectiveness of using eco-enzymes in water irrigation channels by comparing the water quality of areas near the Dukupuntang natural stone industry before and after treatment with eco-enzymes. The approach used in this research is desk study, field survey, Focus Group Discussion (FGD), and laboratory analysis. The data analysis method used in this research is descriptive analysis. The stages of natural stone production are excavation, stone cutting, groove making, and finishing. The process of cutting natural stone waste plays a role in the production of natural stone wastewater. Providing eco-enzyme treatment can reduce soil pH to neutral pH. Color and DO parameters decreased with eco-enzyme treatment. The TSS, TDS, BOD, and COD parameters increased with eco-enzyme treatment.